Fabrication of titanium doped BiVO4 as a novel visible light driven photocatalyst for degradation of residual tetracycline pollutant. Issue 24 (15th December 2021) - Khanh Huyen, Nguyen Thi; Pham, Thanh-Dong; Dieu Cam, Nguyen Thi; Van Quan, Pham; Van Noi, Nguyen; Hanh, Nguyen Thi; Thanh Tung, Mai Hung; Dao, Van-Duong
Abstract: In this study, titanium (Ti) was used as an active dopant to incorporate into BiVO4 lattice using the hydrothermal method. The synthesized BiVO4 and Ti–BiVO4 with 1, 5 and 10 wt% of Ti dopants have been applied for photocatalytic decomposition of Tetracycline under visible light irradiation. The characterized results showed that this synthesized BiVO4 and Ti–BiVO4 materials existed in a form of spherical particles. The particle sizes of the Ti–BiVO4 were much bigger than that of the BiVO4 . However, Ti dopants effectively enhanced visible light absorption, decreased band gap energy as well as prevented electron-hole recombination of the BiVO4 leading to increase in photocatalytic activities of the doped materials. The obtained results from photocatalytic experiments indicated that the 5Ti–BiVO4, whose weight ratio of Ti was 5%, was the best material for TC degradation (78.49%). Recycling tests were consecutively carried out in 4 runs to demonstrate the stability of the BiVO4 photocatalyst with 5 wt% of Ti dopant.